2023
DOI: 10.1590/1413-81232023288.06022023
|View full text |Cite
|
Sign up to set email alerts
|

Consulta de puericultura na Estratégia Saúde da Família em municípios do interior do estado da Paraíba, Brasil

Abstract: Resumo O objetivo deste artigo é avaliar a consulta de puericultura realizada por profissionais de saúde que atuam na Estratégia Saúde da Família em municípios do estado da Paraíba, comparar o desempenho segundo o tipo de equipe de saúde (Programa Mais Médicos ou convencional) e analisar a associação da satisfação do usuário com as ações desenvolvidas. Estudo transversal que avaliou as condições de estrutura das unidades de saúde, o processo de trabalho dos profissionais de saúde e a satisfação do usuário, obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
4

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
2
0
4
Order By: Relevance
“…As famílias em situação de vulnerabilidade socioeconômica podem ter maiores desafios para cumprir todas as recomendações de puericultura, como aquisição de alimentos saudáveis ou cumprimento rigoroso de todas as consultas e exames necessários. Portanto, é fundamental que políticas públicas e sistemas de saúde considerem esses fatores sociodemográficos para garantir uma adesão efetiva à puericultura e igualdade no acesso aos cuidados de saúde infantil (ALBERNAZ; COUTO, 2022;PEDRAZA, 2023).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…As famílias em situação de vulnerabilidade socioeconômica podem ter maiores desafios para cumprir todas as recomendações de puericultura, como aquisição de alimentos saudáveis ou cumprimento rigoroso de todas as consultas e exames necessários. Portanto, é fundamental que políticas públicas e sistemas de saúde considerem esses fatores sociodemográficos para garantir uma adesão efetiva à puericultura e igualdade no acesso aos cuidados de saúde infantil (ALBERNAZ; COUTO, 2022;PEDRAZA, 2023).…”
Section: Resultsunclassified
“…A relação de confiança estabelecida entre o profissional de saúde e a família contribui para a criação de um vínculo saudável e para o fortalecimento do cuidado parental. No entanto, há diversos desafios para a puericultura (PEDRAZA, 2023).…”
Section: Introductionunclassified
“…FNS can be affected by social support, as it is a strategy for promoting access to adequate quantity and/or quality of food by allowing loans of money or food, support in food production and preparation, help in childcare, building connections to find employment, and emotional support that improves the ability to cope with stressful events 22 , 23 , 27 , 28 . In addition, social support has been reported to be important for the adherence to health care and services, as well as environmental control and autonomy 29 . These results highlight social support as a protective factor and the importance of the availability of family and/or friends for FNS, pointing to the need for further research on the subject, given that it is still a recent research topic.…”
Section: Discussionmentioning
confidence: 99%
“…Another study that assessed 175 childcare consultations carried out by PHC professionals identified that, in all consultations, weight, length and head circumference measurements were checked in 96.0% of children. However, assessment of development (21.7%), guidance on growth -weight (38.3%) and development (11.4%), recording in BMI/age curves (11.4%) and milestones development (12.0%), and guidelines related to supplementation (25.7%) and prevention of accidents and violence (2.9%) presented low frequencies of implementation 10 .…”
Section: Introductionmentioning
confidence: 99%